2022
DOI: 10.52965/001c.37518
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health in Urologic Oncology

Abstract: This article is a systematic review of mental health in urologic oncology patients with prostate cancer (PCa), bladder cancer (BC), renal cell carcinoma (RCC), testicular cancer (TC), or penile cancer (PeCa). For all pathologies, a focus on increasing quality of life post-treatment demonstrated a positive impact in reducing Mental Health Illness (MHI) prevalence. Cancer specific mental health care may be given to patients to reduce suicide risk in BC patients and sexual identify and masculinity counseling may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 130 publications
0
4
0
Order By: Relevance
“…Changes in the QoL level of PC patients are driven to a significant extent by PC treatment modalities, and the burden of psychiatric symptoms increases with a more aggressive treatment approach [21]. This leads to alterations in sexual functioning as well as changes in patients' body image and perception of their sexuality [22][23][24][25]. In a study conducted by Opjordsmoen et al, some PC patients reported that if it was possible, they would rather choose to live shorter after treatment but with more preserved sexual function [26].…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the QoL level of PC patients are driven to a significant extent by PC treatment modalities, and the burden of psychiatric symptoms increases with a more aggressive treatment approach [21]. This leads to alterations in sexual functioning as well as changes in patients' body image and perception of their sexuality [22][23][24][25]. In a study conducted by Opjordsmoen et al, some PC patients reported that if it was possible, they would rather choose to live shorter after treatment but with more preserved sexual function [26].…”
Section: Discussionmentioning
confidence: 99%
“…Annually, 1.4 million new cases cast light on the vast number of individuals grappling with the mental health repercussions of such diagnoses. 7,8 Men navigating the aftermath of these diagnoses are often caught in a vicious cycle where the psychological distress from their condition exacerbates physical symptoms, thereby deepening their mental health crisis (Figure 1). Anxiety, depression and stress, amplified by the side-effects of treatments and the existential confrontation with mortality, persist well beyond the medical management of the disease, casting a long shadow over men's recovery and quality of life.…”
Section: Unique Psychological Challengesmentioning
confidence: 99%
“…Men diagnosed with conditions like prostate cancer, which is the second most common cancer globally, find themselves facing not only a physical health battle but also a profound psychological struggle. Annually, 1.4 million new cases cast light on the vast number of individuals grappling with the mental health repercussions of such diagnoses 7,8 . Men navigating the aftermath of these diagnoses are often caught in a vicious cycle where the psychological distress from their condition exacerbates physical symptoms, thereby deepening their mental health crisis (Figure 1).…”
Section: Unique Psychological Challengesmentioning
confidence: 99%
“…In recent history, the global community has confronted unprecedented challenges emanating from the 2019 coronavirus disease (COVID- 19) pandemic, that has brought a cumulative number of 770 million cases and almost 7 million deaths, as of late 2023 [1,2]. The seismic shifts in daily life routines and the healthcare landscape have had profound implications for individuals dealing with chronic illnesses and cancer [3], including those with urological malignancies, marked by its intricate association with various physiological and psychological comorbidities [4][5][6]. Currently, urothelial (bladder) cancer stands as the 10th most common cancer worldwide [7], with a noted increase in incidence, particularly in developed countries where industrial exposures are high [8,9].…”
Section: Introductionmentioning
confidence: 99%